The Influence of R2L-Based HOTS Learning on Narrative Text Writing Skills for Junior High School Students - Hayati, Yenni; Gustia Ningsih, Ayu; Rasyid, Yulianti; Nik Muhammad Affendi, Prof. Madya Datin DR. Nik Rafidah (BAHASTRA, 2025)
This study aimed to describe the effect of implementing the R2L learning model on improving students' writing narrative text skills. The researcher identified the research sample, namely the 7th-grade students of SMPN 13 Padang, totaling 28 students. The researcher collected data by processing the pre-test results from the representations obtained before applying the R2L model and the post-test results obtained after applying the R2L model. The data were analyzed using the Paired T-Test parametric analysis method. The results found are that the Reading to Learn (R2L)-based HOTS learning model can improve students' writing skills and have a significant effect. This is in line with the data found in the field, namely the pretest-posttest results with a value of tcount=-9.682<ttable=-2,052.